Optimizing CNC wood milling operations with the use of genetic algorithms on CAM software. Issue 2 (14th March 2016) - Krimpenis, A. A.; Fountas, N. A.; Mantziouras, T.; Vaxevanidis, N. M.
Abstract: Main focus of this paper is to introduce an appropriate methodology and create a Genetic Algorithm that optimizes wood milling operations, since wood is one of the primary materials used in both structures and musical instruments building. Mechanical properties of wood were considered in the cutting process modeling on CAM software as far as machining parameter values are concerned. Key machining parameters are explained along with their effect on the final product. The proposed Genetic Algorithm was specifically built for wood milling applications and its operators are examined in detail. The undertaken quality characteristics were minimum machining time and optimal surface quality, thus covering both productivity and quality goals at the same time. As a case study, a novel custom 3D CAD model of an electric guitar body was introduced, on which the proposed optimization methodology was implemented, so as to reveal its efficiency and effectiveness.